Atos da fala diretos: recursos persuasivos utilizados pelo enfermeiro para orientação dos pacientes. - Jesus, Suzane Brust de (2009)
This research considers the investigation of the argumentative strategies used by a nurse to persuade the patient and it s a study of qualitative nature with a descriptive approach, aiming to investigate the semantic-discursive function(s) of the direct and indirect speech acts used by the nurse to persuade the patient to follow the recommended behaviors. To reach this objective, the research had the following stages: description of the direct and indirect acts, according to the Speech Acts Theory, used by the nurse to persuade the patient; survey of the recurrent speech acts and inquiry of the argumentative function(s) of the identified acts. The research was based on the Speech Acts Theory of Austin and Searle, that studies the accomplishment of the speech acts as a way to describe what is explicitly said or not said in the linguistic interaction between nurse-patient, identifying which acts predominate (direct or indirect); and, later, in Perelman s Argument Theory, analyzing as these speech acts are used to persuade the patient, with emphasis in the analysis of the relation between nurse and patient, and of how one convinces the other to do the recommended behaviors. The corpus was composed of nursing consultations, recorded in Units of Family Health in the town of Olinda, and it was exclusively analyzed the speech act of the nurse. In the analysis of the corpus one perceives that, during the consultations, three strong moments in the interaction exist. At the beginning of the nursing consultation, there the nurse investigates the patient s health condition to be able to define the clinical picture, the diagnosis, and later the orientation of the behavior to be adopted to solve the detected health problems. These acts are defined as macro-acts of INVESTIGATING, DIAGNOSING, and GUIDING witch are direct speech acts. It was concluded that the direct macro-act of GUIDING is predominant in the nursing consultation, permeating all of the nurse s talks in the interaction with the patient, and it constitutes one of the main attributes of the nursing profession, and the main purpose of the nursing consultation. Also, it was perceived that these acts occur according to the interlocutor, that is, the nurse adjusts the speech according to the particular audience: the patient, trying to adapt it to his/her values, consistent with the context where it was inserted. Therefore, in the analysis of the corpus, it is noted that the nurse uses sentences in the form of direct speech acts to, through argumentation, reach the goal to direct speech acts and persuade the patient, provoking changes of habits and behaviors.